Factors affecting variability in vestibulo-ocular reflex gain in the Video Head Impulse Test in individuals without vestibulopathy: A systematic review of literature - Money-Nolan, Laurel Elise; Flagge, Ashley Gaal (Frontiers in Neurology, 2023)
Introduction The purpose of this systematic review was to summarize and synthesize published evidence examining variations in vestibulo-ocular reflex (VOR) gain outcomes for the Video Head Impulse Test (vHIT) in healthy individuals without vestibulopathy in order to describe factors that may influence test outcomes. Methods Computerized literature searches were performed from four search engines. The studies were selected based on relevant inclusion and exclusion criteria, and were required to examine VOR gain in healthy adults without vestibulopathy. The studies were screened using Covidence (Cochrane tool) and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement standards (PRISMA-2020). Results A total of 404 studies were initially retrieved, of which a total of 32 studies met inclusion criteria. Four major categories were identified which lead to significant variation in VOR gain outcomes: participant-based factors, tester/examiner-based factors, protocol-based factors, and equipment-based factors. Discussion Various subcategories are identified within each of these classifications and are discussed, including recommendations for decreasing VOR gain variability in clinical practice.